Implementasi Model Active Learning Tipe Index Card Match Dalam Pembelajaran Sejarah Kebudayaan Islam - Rifai, Ahmad; Fatkhurrohman, Fatkhurrohman; Fatiatun, Fatiatun (AL-QALAM: JURNAL KEPENDIDIKAN, 2024)
This study aims to investigate the implementation of an active learning model with letter matching in teaching the history of Islamic culture to fourth-grade students at MI Ma'arif Kalibeber Wonosobo. This study was conducted as a field study with a qualitative approach and a descriptive research design. Data were collected through interviews, observations, and documentation. The data sources included class teachers and fourth-grade students from MI Ma'arif Kalibeber Wonosobo. The data analysis method used the interactive Miles & Huberman model, which involved data reduction, data display, data conclusion design, and verification stages. The survey results indicate the following: 1) The implementation of the active learning model with letter matching in teaching SKI to fourth-grade students at MI Ma'arif Kalibeber was successfully carried out. 2) There are supporting and inhibiting factors in the implementation of the active learning model in chip matching. 3) The evaluation method for studying SKI uses a catalog card that corresponds to the active learning model.